2006
DOI: 10.1007/s10681-006-9263-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Brassica napus L. Germplasm from China and Europe assessed by some agronomically important characters

Abstract: The genetic diversity and relationships among 63 rapeseed accessions, including 34 Chinese, 22 Czech, 2 Swedish, 2 German, one French and 2 Canadian accessions, were evaluated by nine agronomically important characters in the field at Yangling, Shaanxi, China. Significant differences between Chinese and European group in plant height, setting position of the first primary branch, number of siliques of the terminal raceme, thousand seed weight and seed yield per plant were detected. There were significant varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 9 publications
3
34
0
1
Order By: Relevance
“…Present findings also revealed that geographic origin of the B. napus accessions had no significant effect on varied grouping of the genotypes. Therefore, cluster is mostly made on traits basis and not based on origin in various Brassica populations (Gupta and Pratap, 2007;Hu et al, 2007;Rabbani et al, 1998b;Dhillon et al, 1999). However, it is also not necessary that the accessions/genotypes grouping always made because of their morphological traits, though some researchers were inconsistent with this opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Present findings also revealed that geographic origin of the B. napus accessions had no significant effect on varied grouping of the genotypes. Therefore, cluster is mostly made on traits basis and not based on origin in various Brassica populations (Gupta and Pratap, 2007;Hu et al, 2007;Rabbani et al, 1998b;Dhillon et al, 1999). However, it is also not necessary that the accessions/genotypes grouping always made because of their morphological traits, though some researchers were inconsistent with this opinion.…”
Section: Discussionmentioning
confidence: 99%
“…It is influenced by genetic and environmental factors, as well as agricultural technology (Hu et al, 2007;Krzymański et al, 2009;Mert-Turk et al, 2008). Changes to the growing environment, as influenced by agronomic practice or the climate, are preventing the genetic potential from being realized (Berry & Spink, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Brassica napus L. (AACC, 2n = 38) is one of the most important oilseed crops in the world, particularly in Canada, Europe, and China (Hu et al, 2007). To date, the consumption of vegetable oil has risen sharply in order to meet the demands of population growth and the developing global economy (Ahmad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%